Three arcs: observations on the archaeology of the Elands Bay and northern Cederberg landscapes - Mackay, A. (Southern African Humanities, 2016)
The area around Elands Bay and the adjacent interior landscapes west of the Doring River have been subject to intense archaeological investigation over the last 50 years. The result is a region with great depth and diversity of archaeological information. In this paper I discuss three general observations that arise from the integration of data across this region. The first is that redundancy in site occupation is limited: even where many sites are excavated in a small area, understanding of the regional sequence cannot be assumed to be complete. The second is that humans did not live in rock shelters: a focus on rock shelters alone, even where these are abundant, produces a skewed picture of occupational and demographic histories. The third is that the coast and its hinterland are intimately bound: interaction between the two zones is variable, and even where it is limited this observation is important to the understanding of both.